PENGARUH BASIS SALEP TERHADAP FORMULASI SEDIAAN SALEP EKSTRAK DAUN KEMANGI ( Ocimum sanctum L.) PADA KULIT PUNGGUNG KELINCI YANG DIBUAT INFEKSI Staphylococcus aureus - Naibaho,, Olivia H; Yamlean, Paulina V. Y.; Wiyono, Weny (PHARMACON, 2013)
The basil plant (Ocimum sanctum L.) contains alkaloids, triterpenoids, flavonoids are able to provide an antibacterial effect.The aims of this research were to study ointment base effect against physical properties and antibacterial effect of basil leaf extract ointment on Rabbits (Oryctolagus cuniculus) back skin infected with staphylococcus aureus.Extraction was done by soxhlet extraction using ethanol 95% as solvent.Observation of healing time was done by observing infectionhealingtime on rabbits back skin after anointment treatment, which based onthe disappearance oferythema and pus. The result shows differences ointment base effected on the physical properties of an ointment which include shape, color, pH, and dispersive power, but had no effect on the smell and homogeneity of the preparation. Basil leaves extract ointment with base type hydrocarbons provide healing infections more quickly, followed by the type of water-soluble base, absorption, and washable base. Keywords: Base ointment, basil (Ocimum sanctum L.), Staphylococcus aureus, rabbit